2020
DOI: 10.1109/access.2019.2962018
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Mobile App Identification Using Deep Learning

Abstract: Many network services and tools (e.g. network monitors, malware-detection systems, routing and billing policy enforcement modules in ISPs) depend on identifying the type of traffic that passes through the network. With the widespread use of mobile devices, the vast diversity of mobile apps, and the massive adoption of encryption protocols (such as TLS), large-scale encrypted traffic classification becomes increasingly difficult. In this paper, we propose a deep learning model for mobile app identification that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 51 publications
0
35
0
5
Order By: Relevance
“…We use a real-world mobile traffic dataset from an ISP, and demonstrate that our approach has an edge over the state-of-the-art in service classification over encrypted web traffic. Table 1 compares the performance of our model with [4] and a traditional baseline.…”
Section: Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use a real-world mobile traffic dataset from an ISP, and demonstrate that our approach has an edge over the state-of-the-art in service classification over encrypted web traffic. Table 1 compares the performance of our model with [4] and a traditional baseline.…”
Section: Contributionsmentioning
confidence: 99%
“…Using our model based on Stacked LSTM layers, we achieve an accuracy of over 95% for classification exclusively over HTTPS (i.e., HTTP/1.1 and HTTP/2 over TLS), outperforming [4] by a significant margin of nearly 50% fewer false classifications. It is also shown that our approach generally achieves higher accuracies as it is less prone to over-fitting.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Для коррекции весов в процессе обучения применяется алгоритм обратного распространения ошибки (backpropagation). Для работы с большим количеством параметров во внутренних слоях сети или для определения инвариантных относительно переноса признаков свою эффективность показали свёрточные нейронные сети (CNN), использующие набор небольших ядер для преобразования поступающей информации и уменьшения числа извлекаемых признаков [12,23,[27][28][29][30].…”
Section: нейронные сетиunclassified
“…The technique can be exploited by an adversary for malicious purposes like recognizing potentially sensitive or vulnerable apps. With the problem of APP-ID receiving increasingly attention, there has emerged considerable related works in recent years [2]- [18].…”
Section: Introductionmentioning
confidence: 99%